Estimated doses of radiation received by the eye lens during endourological procedures: Are we being careful enough? ESUT-YAU endourology group collaboration - ŞENER, TARIK EMRE (My University, 2022)
NTRODUCTION AND OBJECTIVE: The protection of the lens during interventional radiology procedures has become an aspect of special concern since the appearance of cataracts at relatively low doses (below 0.1 Gy). Current knowledge about radiosensitivity of the eye lens has led the European Atomic Energy Community (EURATOM) to reduce the annual limit of equivalent dose for the eye lens from 150 mSv/year to 20 mSv/year. Our objective is to estimate the radiation doses received by the lens during endourological procedures to determine if endourologists comply with current recommendations. METHODS: A multicenter study was conducted recollecting the prospective data of annual dosimeters between 2017 and 2020. Four endourologists used an eye dosimeter to estimate radiation doses received by the lens in all endourological procedures, including ureteroscopy (URS), retrograde intrarenal surgery (RIRS) and percutaneous nephrolithotomy (PCNL). Two of them wore leaded protection glasses while two of them did not; in addition, one of the surgeons used a fluoroless protocol. Statistical analysis was performed using SPSS 22.0. RESULTS: Surgeons 1, 2, 3 and 4 performed a median of 158.5, 585.5, 102.0 and 129.0 endourological procedures, respectively, for a total of 641, 2,340, 413 and 350 between 2017 and 2020. The mean annual dose of lens radiation exposure for Surgeon 1, 2, 3 and 4 was 0.16, 1.18, 3.79 and 1.41 mSv per year, which corresponds to 0.001, 0.002, 0.032 and 0.014 mSv per procedure. The two surgeons who used leaded glasses registered a lower radiation dose per procedure (0.001 vs. 0.027). Similarly, the urologist who used a fluoroless protocol registered a lower lens radiation dose compared to the three surgeons who did not use it (0.001 vs. 0.023). CONCLUSIONS: According to our study, endourologists successfully comply with current recommendations on radiation exposure to the eye lens. Leaded glasses as well as a fluoroless protocol may further reduce radiation doses. Eye protection glasses may be recommended for radiation protection as well as for exposure to fluids.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Medicine; Health Sciences; Internal Medicine Sciences; Internal Diseases; Nephrology; ÜROLOJİ VE NEFROLOJİ; Klinik Tıp; Klinik Tıp (MED); UROLOGY & NEPHROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Üroloji; Urology